Implementation an Outcome Based Education (OBE) Lesson Plan in English Language Teaching - Bestari, Ade Christanty Yudha; Faiza, Dinar; Mayekti, Meilina Haris (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
This study shows the design and implementation of Outcome-Based Education (OBE) lesson plans in English language teaching. OBE focuses on measurable learning outcomes, which may improve English proficiency. The paper analyzes the development process of OBE-based lesson plans and their efficacy through empirical data, discussing implications for English language teaching. Findings indicate that OBE-based lesson planning enhances clarity in learning objectives, aligns assessments with targeted competencies, and encourages student-centered activities. An OBE framework enhances English language learning by promoting clear, competency-based objectives, interactive activities, and continuous assessment. OBE lesson plans guide students through targeted learning experiences that build relevant language skills. Implementing OBE in ELT requires significant investment in teacher training and resources to support lesson planning and assessment restructuring. Challenges like lecturer readiness and resource allocation are acknowledged. OBE in ELT has shown potential to improve teaching and learning by promoting competency-based instruction and student-centered activities. Addressing challenges like time constraints and professional development is crucial for this approach’s sustained success.